Plasma Secretagogin is Increased in Individuals with Glucose Dysregulation - Yang, Chao; Qu, Hua; Zhao, Xiaolan; Hu, Yingru; Xiong, Jiayao; Jiang, Xianshu; Chen, Yanmei; Li, Zhiyong (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Secretagogin, a Ca2+ binding protein, is one of the most abundant proteins in pancreatic β-cells and is critical for maintaining the structural integrity and signaling competence of β-cells. This study seeks to assess the concentrations of plasma secretagogin in participants with prediabetes (pre-DM) and newly diagnosed type 2 diabetes (T2DM) and to explore its relationship to parameters of glucose and lipid metabolism, first-phase insulin secretion, insulin resistance and pancreatic β-cell function.Materials and Methods A total of 126 eligible subjects were divided into three groups: a normal glucose tolerance (NGT, n=45), a pre-DM (n=30), and a T2DM (n=51) group. An intravenous glucose tolerance test (IVGTT) was performed, and clinical and biochemical parameters were measured for all subjects.Results Plasma secretagogin levels were significantly higher in both pre-DM and T2DM patients compared with NGT subjects and were highest in the T2DM group. Correlation analysis showed that plasma secretagogin levels were positively correlated with fasting plasma glucose, postchallenge plasma glucose (2hPG), HbA1c and body mass index (BMI) but were not correlated with waist-hip ratio, blood pressure, lipid profiles, fasting serum insulin, homeostasis model assessment for insulin resistance, homeostasis model assessment for β-cell function and first-phase insulin secretion indicators. Multiple logistic regression analysis revealed that 2hPG and BMI were independent predictors for elevation of plasma secretagogin concentrations.Conclusions Increased circulating secretagogin might be a molecular predictor for early diagnosis of diabetes. Further studies are needed to confirm this finding and explore the role of secretagogin in obesity.
Keywords: secretagogin; diabetes; prediabetes; insulin secretion; obesity